A review on proteolytic fermentation of dietary protein using lactic acid bacteria for the development of novel proteolytically fermented foods - Zhi, Yin Ter; Lee, Sin Chang; Babji, Abdul Salam; Mohd Zaini, Nurul Aqilah; Fazry, Shazrul; Sarbini, Shahrul Razid; Peterbauer, Clemens Karl; Seng, Joe Lim (Wiley-Blackwell Publishing, 2024)
Bioactive peptides generated from food proteins have gained much interest as functional foods. Recently, the application of lactic acid fermentation has developed rapidly thanks to the discovery of probiotic functions in lactic acid bacteria (LAB). Aside from converting a fermentable carbohydrate into lactic acid, many strains of LAB were found to possess proteolytic activity, which is essential for many fermentation processes. The protease enzymes produced from the proteolytic fermentation breakdown proteins in food and generate a variety of high-value products which are discussed in this review. These substances give rise to the production of functional food that exerts diverse health benefits including antioxidant, antihypertension, antihyperglycaemic, antiinflammation, antimicrobial, and anticancer effects. The effects of proteolytic fermentation on the physicochemical and functional properties, biological activities, and sensory attributes of foods are elaborated in this review article. The application of proteolytic fermentation in various food industries, mainly the dairy industry, meat industry, bakery industry, and brewing industry, improved the technological, nutritional, biological, and sensory characteristics, as well as increased the shelf life of food. Ultimately, this review summarises in-depth knowledge of proteolytic fermentation by LAB and generates additional interest in the development of novel proteolytically fermented products.